Penguasaan Tanah Sebagai Barang Milik Daerah oleh Pemerintah Kota Padang - Hardi, Imelda; Warman, Kurnia; Andora, Hengki (Universitas Ekasakti, 2023)
This research focuses on; 1) control and management of Government Land by the Regional Government, 2) control of Regional Government Land by the Padang City Government, and 3) control and security of Regional Government Land which can create legal certainty and provide maximum benefits. The research method in this study uses a normative juridical, empirical, and conceptual approach. The data sources used come from regulations, documents relating to the management of land assets as well and the results of interviews with parties involved in the management of Regional Property in the form of land of the Padang City Government. Based on research that has been carried out, the implementation of the management of Regional Government land assets has been carried out by the Padang City Government through regulations governing the management of Regional Property. However, several obstacles cause less than optimal management of land assets by the Padang City Government by OPD land users. Furthermore, 3 (three) efforts to secure land assets must be implemented as an inseparable unit, so that legal certainty of land assets of the Padang City Government can be achieved which can provide maximum benefits.